PENGISIAN OTOMATIS MENGGUNAKAN LOAD CELL UNTUK BEBERAPA JENIS UKURAN BOTOL BERBASIS SCADA - Daud Sibrani (Prosiding Industrial Research Workshop and National Seminar, 2019)
Automatic bottle filling is a very influential factor in the beverage production process in both the middle and lower industries. The human error factor causes the production process to be hampered and unstable. The purpose of the tool that will be made is to monitor the production process to be more effective and efficient. The monitoring and control system on this tool uses a SCADA-based system (Supervisory Control And Data Acquisition) and an on-off control system. In this tool using several sensors and actuators to monitor and control the plant, including the heavy sensor (load cell), proximity sensors, ultrasonic sensors, motors, and solenoid valve. The sensor will send data to the RTU (Remote Terminal Unit) which then the data will be displayed on the HMI (Human Machine Interface). The bottles that will be filled consist of 3 types, namely large bottles weighing 1000 gr, medium bottles weighing 500 gr, and small bottles weighing 300 gr, and ultrasonic sensors will measure the height of the water and the data obtained will be displayed on the HMI. With the making of this tool, it is expected that the condition of the plant can be monitored easily